I Don't Wanna Die - Kilgore, Vincent Max (East Carolina University, 2021)
This story attempts to shine a light on the injustices faced by the LGBT community through the tale of an aspiring Drag Queen. Fed up with his mundane life as a Universal park employee by day and bus boy by night, Cameron Demarco sets out on his journey in the world of drag to hopefully pull himself out of the life he has been forced into. Along with his trusted "fairy-drag-mother," Karina el Vira, he must learn to sashay down the runaway of life before it all passes him by.
Keywords: Drag queens--Fiction; Sexual minorities in literature; Sexual minorities--Social conditions